Communication and patient safety in an Intensive Care Unit: prospects of the multiprofissional health team (Research, Society and Development, 2021)
The objective of this study was to evaluate the patient safety culture related to communication in an Adult Intensive Care Unit of a hospital in the interior of the state of Rio Grande do Sul from the perspective of the multiprofessional health team. This is a survey study, carried out in October 2019, which used the Hospital Survey on Patient Safety Culture questionnaire for data collection, and for the purposes of this study, the dimensions "Openness to communication" and "Shift and internal transfers" were evaluated, thus constituting 7 items.  The survey had the participation of 54 health professionals, being the majority nursing technicians (48.15%), female (75.93%), aged between 20 and 29 years (61.11%), with time of work in intensive care units between 1 and 5 years (46.30%). The dimension "openness for communication" received and 59.26% of positive answers, being considered neutral and the dimension "change of shifts and internal transfers" received 33.80%, being considered fragile. It was evident that in the analysis of the two dimensions there are weaknesses in patient safety in the intensive care unit in the aspect evaluated, highlighting the need to discuss the issue in the unit under study and in all units of the hospital.